2021
DOI: 10.1080/15257770.2021.1952596
|View full text |Cite
|
Sign up to set email alerts
|

HMGA2 rs968697 T > C polymorphism is associated with the risk of colorectal cancer

Abstract: Background: Recently, a genetic polymorphism (rs968697 T>C) in HMGA2 gene has been reported to be associated with hepatoblastoma risk. However, no studies reported the effect of the polymorphism on the risk of colorectal cancer (CRC). The study aimed to explore whether rs968697 polymorphism had a signi cant impact on CRC risk. Methods: A total of 500 CRC patients and 500 age and gender matched healthy individuals were genotyped by Sanger sequencing. Quantitative real-time PCR technology was used to detect the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…GC patients carrying the rs968697 CT and Recent studies have shown that the HMGA2 rs968697 genetic polymorphism could reduce susceptibility to digestive tumors, including hepatoblastoma and colorectal cancer. 14,15 However, the findings in other malignancies were inconsistent and needed to be clarified by meta-analysis. The current meta-analysis showed that the rs968697 genetic polymorphism was linked to malignancy susceptibility in the Chinese population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…GC patients carrying the rs968697 CT and Recent studies have shown that the HMGA2 rs968697 genetic polymorphism could reduce susceptibility to digestive tumors, including hepatoblastoma and colorectal cancer. 14,15 However, the findings in other malignancies were inconsistent and needed to be clarified by meta-analysis. The current meta-analysis showed that the rs968697 genetic polymorphism was linked to malignancy susceptibility in the Chinese population.…”
Section: Discussionmentioning
confidence: 99%
“…The primer sequences are displayed in Table S1. 14 The mRNA expression levels were calculated using the 2 ÀΔΔCt approach. GAPDH expression levels were used as internal controls.…”
Section: Genotype-tissue Expression Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Te occurrence and development of CRC is a complicated and multidimensional process, and epidemiological studies have found multiple risk factors associated with the occurrence of CRC, including various unhealthy diets and lifestyles [2]. In addition, previous genomics studies have revealed that single nucleotide polymorphisms (SNPs) in several CRC-related genes are linked to the risk and progression of CRC [3][4][5][6][7][8]. For instance, the interleukins-17A (IL-17A) rs2275913 G > A polymorphism was associated with the occurrence and severity of CRC in the Bulgarian population [6].…”
Section: Introductionmentioning
confidence: 99%
“…Cancer is one of the most serious public health issues in the world, with approximately 18.1 million new cancer diagnoses and 9.6 million cancer deaths in 2018 ( 1 ). Although the precise processes of cancer development and progression are still largely unclear, a growing body of research suggests that genetic predisposition has a substantial influence on the likelihood of individual cancer development ( 2 , 3 ).…”
Section: Introductionmentioning
confidence: 99%